The Effects of Dietary Electrolyte Balance on Performance of Laying Hens Exposed to Heat - Stress Environment in Late Laying Period - Nobakht, A.; Shivazad, M.; Chamany, M.; Safameher, A.R. (International Journal of Poultry Science, 2006)
This study was conducted to determine the effects of different dietary electrolyte balance on performance and eggshell quality of laying hens in heat stress condition. four diets were formulated using different inclusions of NaCl, NaHCO3, KHCO3 and NH4Cl to give the dietary electrolyte (DEB) as 0, 120, 240 and 360 mEq/kg, and fed to laying hens from 55 weeks to 65 weeks of age exposed to heat - stress environment. Egg production, feed intake, water consumption, egg mass and feed conversion ratio were not significantly affected by the diets of various DEB (P>0.05). Among egg parameters shell weight/surface area, shell weight, shell thickness and egg specific gravity were significantly affected by DEB (P< 0.01). In conclusion, increasing dietary electrolyte balance to 360 mEq/kg in laying hens rations under heat stress condition in late period of production can improve egg quality.